Fulfilling Child Rights Post-Divorce in Religious Courts Based on People's Economic Factors after Pandemic - Nurmala Hak; Qadariyah Barkah (Fakultas Syariah UIN Fatmawati Sukarno Bengkulu, 2023)
This writing aims to understand and analyze the Implementation and Obstacles of the Letter of the Directorate General of the Religious Courts Number 1669/DJA/HK.00/5/2021 Concerning the Enforcement of Guarantees to Protect the Rights of Women and Children Post-Divorce, bearing in mind that the community's economy after the pandemic will impact post-divorce children's rights at the Tulang Bawang Tengah Religious Court. This writing uses normative qualitative research methods with rule and case study approaches. The results of the first study found that the Implementation of the Letter of the Director General of the Religious Courts Number 1669/Dja/Hk.00/5/2021 concerning Guarantees for the Fulfillment of Children's Rights Post-divorce at the Tulang Bawang Tengah Religious Court after the pandemic has fulfilled the spirit of fulfilling children's rights after divorce on a few notes. The results of the second study found inhibiting factors such as the Petitum for divorce cases not entirely containing demands for fulfilling children's rights after divorce because the Petitum for divorce cases did not include the fulfilment of the rights of women and children after divorce, Determining the value of living for wives and children due to divorce which still varies, Aspects of implementing the decision (execution) if one of the parties is not present, and the Judge's understanding of the Ultra Petitum Partium Principle. Tujuan penulisan ini adalah memahami dan menganalisis Implementasi dan penghambat dari Surat Direktorat Jenderal Badan Peradilan Agama Nomor 1669/DJA/HK.00/5/2021 Tentang Pemberlakuan Jaminan Perlindungan Hak-Hak Perempuan Dan Anak Pasca Perceraian, mengingat ekonomi masyarakat setelah pandemi akan berdampak dengan hak anak pasca perceraian di Pengadilan Agama Tulang Bawang Tengah. Penulisan ini menggunakan metode penelitian kualitatif normatif dengan pendekatan aturan dan studi kasus. Hasil penelitian pertama menemukan Implementasi Surat Direktur Jenderal Badan Peradilan Agama Nomor 1669/Dja/Hk.00/5/2021 tentang Jaminan Pemenuhan Hak-Hak Anak Pasca perceraian di Pengadilan Agama Tulang Bawang Tengah pasca pandemi adalah telah memenuhi semangat pemenuhan hak-hak anak pasca perceraian dengan beberapa catatan. Hasil penelitian kedua menemukan faktor penghambat seperti Petitum gugatan perkara Cerai belum seluruhnya berisi tuntutan pemenuhan hak anak pasca perceraian, karena Petitum perkara perceraian belum mencantumkan tentang pemenuhan hak-hak perempuan dan anak pasca perceraian, Penentuan nilai nafkah bagi isteri dan anak akibat perceraian yang masih bervariasi, Aspek pelaksanaan putusan (eksekusi) bila tidak dihadiri salah satu pihak, dan pemahaman Hakim Terhadap Asas Ultra Petitum Partium